Growing up in chronic poverty: a qualitative look at its impacts on children - Yaşa, Yeşim. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2007., 2007)
The study aimed to explore the distress and happiness areas and coping strategies of children growing up in chronic poverty through their own voices in order to have a more complete understanding of the effects of poverty on children. Ten qualitative in-depth interviews were realized with 11-12-year-old children, whose families migrated to Istanbul after 1990s, and were living in Tarlabaşı. The data was analyzed using Grounded Theory (Strauss and Corbin, 1998). The results indicated that while several aspects of family relationships, friendships, schools and neighborhoods were sources of troubling areas in the children’s lives; other aspects of the same themes were the sources of happiness as well as support in helping to diminish the impact of disadvantage on their well-being. In response to varied adversities in their lives, children were found to more often use emotion-focused coping strategies. Some children also employed problem-focused strategies. The children who more often used problem-focused strategies had more supportive relations and did not suffer from severe familial problems. The emergent themes revealed that there were variations in children’s experiences of social and material deprivations, problems and coping ways. This suggested that several mediating factors such as parent-child communication, family’s social support network, extended family and communication with peers influenced the way the children experienced the context they were growing up. Hence, the interaction of mediating factors, personal experiences and coping strategies seems to determine the impact of poverty on children’s lives.
Keywords: Poor children -- Turkey.